Structural model of perishable food supply chain quality (PFSCQ) to improve sustainable organizational performance. Issue 7 (1st October 2018) - Siddh, Man Mohan; Soni, Gunjan; Jain, Rakesh; Sharma, Milind Kumar
Abstract : Purpose: The purpose of this paper is to examine the concept of perishable food supply chain quality (PFSCQ) and to suggest a structural model that counts the influence of PFSCQ practices on organizational sustainable performance. Design/methodology/approach: On the basis of comprehensive literature review, PFSCQ highly significant practices were examined and designated. These practices were classified into four dimensions: upstream quality (supplier quality), downstream quality (customer focus), internal quality (process and logistics quality) and support practices (top management leadership and commitment to quality, quality of human resource, quality of information and supply chain integration). The measurement instrument of organizational sustainable performance was also build on, containing three aspects: economic, environmental and social performance. Findings: An inventive conceptual model that specifies a comprehensive image cover up core dimensions of PFSCQ and various aspects of organizational sustainable performance was suggested. This conceptual model can be used as "a directive" for theory developing and measurement instrument development of PFSCQ practices and organizational sustainable performance. More prominently, on the road to achieving additional insight, an extensive structural model that makes out direct and indirect relationships between PFSCQ practices and organizational sustainable performance was also developed. Practitioners can apply this model as "a path plan" for implementing PFSCQ practices to improve organizational sustainable performance. Originality/value: The integration of quality and supply chain even now remains inadequate in the literature. Consequently, it is required to have a more focused approach in assessing quality issues inside the upstream, internal and downstream of the supply chain. This study concentrates on the practices which make better quality aspects of the supply chain, known as PFSCQ practices. Suggested research models in this paper contribute to conceptual frameworks for theory building in PFSCQ and sustainable organizational performance. It is also expected that this research can suggest a useful direction for determining and implementing PFSCQ practices as well as make possible further studies in this arena.